Comprehensive Sexuality Education: A pending matter in Early Childhood Education in Mexico - Salinas-Quiroz, Fernando (2016)
This paper stresses the need to incorporate Comprehensive Sexuality Education(CSE) during the Early Childhood and Preschool school stages in Mexico. Adetailed analysis of the content of strategies, courses of action and policies forearly education was made for both, the local and Latin-American level. Findingsindicate that there remains a need for CSE for 0 to 6-year-old Mexican children.The inclusion of a human rights and a sociocultural perspective of genderedsexuality is strongly recommended. Early life-course interactions between childrenand their caregivers have the potential to influence developmental outcomes in anenduring manner because they become internalized in the form of generalizedmental representations. CSE encompasses the history of care where consistent andcoherent secure base support is needed.